Immune restoration in human immunodeficiency virus and hepatitis C virus coinfected patients after highly active antiretroviral therapy - Antonello,Vicente Sperb (2013)
OBJECTIVE: To evaluate the influence of hepatitis C virus on immunological and virological responses after highly active antiretroviral therapy initiation in human immunodeficiency virus/hepatitis C virus coinfected patients compared to monoinfected human immunodeficiency virus-infected patients. METHODS: The study enrolled 65 human immunodeficiency virus-1-infected subjects who initiated highly active antiretroviral therapy and attended follow-up visits over 48 weeks from 2008 to 2010. They were grouped based on hepatitis C virus-RNA results. Virological and immunological responses were monitored at baseline and at the end of weeks 12, 24, 36, and 48. RESULTS: There were 35 human immunodeficiency virus monoinfected and 30 human immunodeficiency virus/hepatitis C virus coinfected patients. In the present study human immunodeficiency virus/hepatitis C virus coinfection did not seem to influence CD4 Tlymphocytes recovery. There was no difference between the curves of CD4 T-lymphocytes raise of coinfected and monoinfected groups. CONCLUSION: This prospective study confirms that hepatitis C virus infection does not seem to be associated with impaired CD4 T-lymphocytes recovery after HAART.